Horticultural crop health and yield and greenhouse soil conditions after 17 years of repeated treatments of biofumigation and solarization - Mitidieri, Mariel Silvina; Brambilla, Maria Virginia; Barbieri, Martin Osvaldo; Piris, Estela Beatriz; Celie, Ramón Enrique; Peralta, Romina (2023)
Link al video de la presentación: https://youtu.be/sM436c_5JCM